Predicting Treatment Success with Facet Syndrome: An Algorithm to Predict Lumbar Radiofrequency Ablation Responders in a Military Population. Issue 2 (9th November 2020) - Hughey, Scott; Cole, Jacob; Booth, Gregory; Moore, Jeffrey; McDowell, Benjamin; DeYoung, Henry; Hosig, Anna; Moran, Thomas; Stedje-Larsen, Eric
Abstract: Objective: Radiofrequency ablation (RFA) of the medial branch nerve is a commonly performed procedure for patients with facet syndrome. RFA has previously been demonstrated to provide long-term functional improvement in approximately 50% of patients, including those who had significant pain relief after diagnostic medial branch block. We sought to identify factors associated with success of RFA for facet pain. Design: Active-duty military patients who underwent lumbar RFA (L3, L4, and L5 levels) over a 3-year period were analyzed. Defense and Veterans Pain Rating Scale (DVPRS) and Oswestry Disability Index (ODI) scores were assessed the day of procedure and at the 2-month and 6-month follow-up. These data were analyzed to identify associations between patient demographics, pain, and functional status and patients' improvement after RFA, with a primary outcome of ODI improvement and a secondary outcome of pain reduction. Results: Higher levels of starting functional impairment (starting ODI scores of 42.9 vs. 37.5; P = 0.0304) were associated with a greater likelihood of improvement in functional status 6 months after RFA, and higher starting pain scores (DVPRS pain scores of 6.1 vs. 5.1; P < 0.0001) were associated with a higher likelihood that pain scores would improve 6 months after RFA. A multivariate logistic regression was then used to develop a scoring system to predict improvement after RFA. The scoring system generated a C-statistic of 0.764, with starting ODI, pain scores, and both gender and smoking history as independent variables. Conclusions: This algorithm compares favorably to that of diagnostic medial branch block in terms of prediction accuracy (C-statistic of 0.764 vs. 0.57), suggesting that its use may improve patient selection in patients who undergo RFA for facet syndrome.